Unraveling the Dynamics of Performance Measurement: A Qualitative Study on Adopting Continuous and Datadriven Approaches in Performance Management - Adawiyah, Andi (Manunggal Halim Jaya, 2024)
This qualitative research explores the dynamics of performance measurement within organizations, focusing on the adoption of continuous and data-driven approaches. The study aims to understand the significance of real-time feedback, predictive analytics, and organizational culture in enhancing performance management practices. The research methodology involves a comprehensive literature review, synthesizing insights from diverse sources such as scholarly articles, books, and reports. Purposive sampling is employed to select relevant literature on performance measurement, data analytics, and organizational behavior. Data collection involves systematically gathering and analyzing information from selected sources, using techniques like content analysis and thematic coding. The findings highlight the importance of continuous performance measurement in driving organizational agility and strategic alignment. Additionally, the study identifies challenges related to data integration, quality assurance, and cultural resistance that organizations face in adopting data-driven approaches. Technological advancements, particularly in predictive analytics and machine learning, offer promising solutions to address these challenges and enhance performance measurement effectiveness. Overall, the research contributes to theoretical understanding and managerial practice by providing insights into the role of real-time feedback, predictive analytics, and organizational culture in performance management.